Model Inovasi Pengembangan Lingkungan Belajar Pendidikan Islam: Penelitian - Ali Makki; Nurul Layli R (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This article discusses many models of innovation development in Islamic education of learning environments. Innovation in the development of learning environments is an effort to change the learning process of students systematically by making the potential of the existing environment into something better in the learning system, so that students are expected to be able to develop and progress. In the development of Islamic educational environments, the main goal is an effort to form character and change student behavior in the learning process towards achieving the desired success. In a learning environment, it is necessary to develop a learning environment with new models that are easy for students to respond to and without changing the role of the environment around them, because in learning there are always changes and discrepancies between the theory presented and the reality of the facts in the field. This study is part of the relevance of the innovation development model to the Islamic educational learning environment in the theories of educational experts. The purpose of this study is to determine and explain the innovation development model for the learning environment of students in Islamic education. The method used in this study is qualitative with the type of library research.